Male Writers of DānměiLiterature: An Analysis of Fēitiānyèxiáng - Aiqing Wang (Center for Research and Development of Religious Literature and Heritage, 2021)
In this paper, I investigate dÄnmÄ›i as a ground-breaking literary genre by means of scrutinising an illustrious male writer pseudonymed FÄ“itiÄnyÃ¨xiÃ¡ng, and I propound that his works are exemplary as online writing. As a growing Chinese Internet literature, the female-oriented dÄnmÄ›i genre, aka Boys Love, has attracted legions of heterosexual fangirl producers and consumers as well as a meagre amount of their male counterparts. Among male dÄnmÄ›i writers, who are in an absolute minority, FÄ“itiÄnyÃ¨xiÃ¡ng is celebrated for a wide range of innovative themes and magnificent storylines, and his fiction is replete with profound literary and historical allusions and elaborate and meticulous depictions. Furthermore, notwithstanding a non-reversible bipartite dichotomy between seme (top) and uke (bottom) roles, FÄ“itiÄnyÃ¨xiÃ¡ng’s writing is not featured by feminisation of uke, which is clichéd characterisation in not only the dÄnmÄ›i subculture, but also classical and modern Chinese literature. More significantly, FÄ“itiÄnyÃ¨xiÃ¡ng’s narratives are reality-oriented, addressing adverse circumstances in a real-world context and hence rendering characters more multi-faceted, and he does not circumvent realistic issues or create over-romanticised representation, analogous to his equivalent pseudonymed NÃ¡nkÄngbÃ¡iqÇ.